Self-emulsifying micelles as a drug nanocarrier system for itraconazole oral bioavailability enhancement; in vitro and in vivo assessment - Nayyer Islam; Naveed Ullah Khan; Anam Razzaq; Zaheer Ullah Khan; Farid Menaa; Mohammad Y. Alfaifi; Serag Eldin I. Elbehairi; Haroon Iqbal; Jiang Ni (Saudi Pharmaceutical Journal, 2023)
Itraconazole (ITZ) is a renowned antifungal medication, however its therapeutic efficacy is limited by low solubility and oral bioavailability. The current research work attempted to augment the oral bioavailability of ITZ by incorporating into self-emulsifying micelles (SEMCs). To fabricate the SEMCs, various preparation techniques including physical mixture, melt-emulsification, solvent evaporation and kneading, were opted by using different weight ratio of drug and solubilizers i.e. Gelucire-50/13 or Gelucire-44/14 and characterized both in vitro and in vivo. The prepared SEMCs were found to be in the size range from 63.4 ± 5.2 to 284.2 ± 19.5 nm with surface charges ranging from −16 ± 1.2 to −27 ± 2.0 mV. The drug solubility was improved to a reasonable extent with all investigated formulations, however, SEMCs in group 6 prepared by kneading method (KMG6) using Gelucire-44/14: drug (10:1 presented 87.6 folds’ increase (964.93 ± 2 μg/mL) compared to solubility of crystalline ITZ (11 ± 2 μg/mL) through kneading method. In addition, KMG6 SEMCs shows the fast drug release compared to other SEMCs. Further, KMG6 SEMCs also exhibited 5.12-fold higher relative intestinal serosal fluid absorption compared to crystalline ITZ. The pharmacokinetic parameters such Cmax, AUC and Tmax of KMG6 SEMCs significantly improved compared to crystalline ITZ. In conclusion, the manipulation of ITZ solubility, dissolution rate and absorption using SEMCs is a promising strategy for bioavailability enhancement.